The Conflict over Resources in Sudan between Major Powers - Economic Impacts and Geopolitical Consequences - Sofiane BELMADI,; Hichem KADRI, (Journal of North African Economies, 2025)
Energy sources are not only crucial for economic development but also significant in shaping the policies of both producing and consuming countries. These strategic resources have the power to influence the decision-making processes, in cases of cooperation, competition, and even conflict. Sudan, in particular, has recognition as a region of contentions, with major powers engaging in fierce competition over its resources. thus, the country's lands have become battlegrounds of varying intensity, as different stakeholders strive to secure their access to and control over these valuable energy sources. By focusing on Sudan as a case study, where there are numerous vital resources and a multitude of competitors, it can gain insights into the nature of geoeconomic competition and the factors contributing to the stagnation of development in the country, as it can uncover the underlying dynamics and potential strategies for promoting growth and maximizing Sudan's potential.